The Impact of Different Irrigation Regimens on the Chemical Structure and Cleanliness of Root Canal Dentin - Elgawish, Amira; Tawfik, Hossam; El Gendy, Abeer; George , Roy; Bakr, Mahmoud (Iranian Endodontic Journal, 2023)
Introduction: This in vitro study aimed to evaluate the effect of different irrigation regimens on the chemical composition and cleanliness of root canal dentin. Materials and Methods: Forty-eight extracted single-rooted permanent human teeth were collected. Root canals were instrumented using step-back technique up to master apical file size 60. Samples were divided into 3 groups (n=16) based on the type of the irrigant used. The irrigation solutions were 5.25% sodium hypochlorite, 2% chlorhexidine gluconate, and saline solution as a control. Root canal cleanliness was assessed using stereomicroscope and scanning electron microscope. Scanning electron microscope energy dispersive X-ray was used for the inorganic analysis. Fourier transform infrared spectrometer was used for the organic analysis. One-way analysis of variance (ANOVA) and multiple comparison post hoc test were used for comparison between the three groups. Results: The highest mean percentage of remaining debris was in saline group followed by chlorhexidine gluconate group. Sodium hypochlorite group showed the lowest mean value of remaining debris. Furthermore, our results showed that canal irrigation with sodium hypochlorite affected the chemical structure of root canal dentin more than chlorhexidine gluconate. Conclusions: Based on the results, 5.25% sodium hypochlorite emerges as the preferred irrigant for root canal treatment. This research sheds light on the significance of irrigation regimens in endodontics and emphasizes the need for careful consideration of irrigant selection in clinical practice.